Countries adoption of the International Financial Reporting Standard for Small and Medium-sized Entities (IFRS for SMEs) - Early empirical evidence - Kaya, Devrimi; Koch, Maximilian (Accounting and Business Research, 2015)
The International Financial Reporting Standard for Small and Medium-sized Entities (IFRS for SMEs) is increasingly being adopted in a number of jurisdictions. Despite the economic importance of non-publicly accountable entities, little is known about what factors influence countries' decisions to adopt IFRS for SMEs. In a unique sample of 128 countries, we find that countries that are not capable of developing their own local generally accepted accounting principles are more likely to adopt IFRS for SMEs. We also provide evidence that in jurisdictions where full IFRS have been applied to private firms, the likelihood of adoption of IFRS for SMEs increases, suggesting that jurisdictions reduce the financial reporting burden on SMEs. Moreover, in line with prior literature, there is evidence that countries with a relatively low quality of governance institutions are more likely to adopt this new set of accounting standards. The results also hold under alternative measures and different estimation approaches. Overall, our results are helpful in understanding the worldwide diffusion of IFRS for SMEs. Standard setters and regulators might consider our study in the future development of accounting harmonisation of non-publicly accountable entities.
CRIS-Team Scopus Importer:2024-03-11
Keywords: Accounting harmonisation; Accounting regulation; IASB; IFRS for SMEs; Nonpublicly accountable entities; Standard setting